GREEN TEA LEAF BREW TEST (CAMELIA SINENSIS L.) AT KIDNEY MICE GIVEN MONOSODIUM GLUTAMATE (MSG) - Reza Anindita (Borneo Journal of Pharmascientech, 2019)
ABSTRACT This research aims to test the potential of green tea in the mice that are given by MSG. Duration of research is 30 days using animal test mice male strains BALB/C. This study uses a complete randomized draft (RAL) factorial. Each treatment consists of P0 as a control given akuades 0.5 ml/w/day, P1 that was given green tea 0.015 gr/bb/day, P2 that were given MSG 0.84 gr/w/day, P3 which was given MSG 0.84 gr/w/day and Green tea 0.015 gr/bb/hr. Results showed that the treatment of MSG doses 0.084 gr/w/day is capable of lose renal weight and increasing glomerular diameter and proximal tubule. Treatment of brewing green tea leaves a dose of 0.015 gr/w/day in mice that are given MSG or without being given the treatment of MSG able to increase renal weight and lower glomerular diameter and proximal tubule. Statistical analysis showed no significant difference (P > 0.05) in the kidneys that was given the brew of green tea leaves in mice that were given MSG or without without being given MSG treatment. The conclusion in this study is the treatment of brewing tea leaves Green dose 0.015 gr/bb/hr is able to reduce the degeneration of renal tissue that is given MSG dose 0.084 gr/bb/hr. Keywords: green tea, MSG, proximal tubule, glomerular and kidney